Research status of rare earth oxides used in Al2O3 wear-resistant ceramics - ZHANG Wei (矿业科学学报, 2025)
Rare earth oxides mainly exist in nature in the form of minerals. Doping rare earth oxides into Al2O3 ceramics can affect their wear resistance. In order to broaden the application scope of rare earth oxides, this paper summarizes the current status of rare earth oxides used in Al2O3 wear-resistant ceramics based on relevant research on the influence of doped rare earth oxides on the wear resistance of Al2O3 ceramics. Firstly, the influencing factors of the wear resistance of Al2O3 ceramics are summarized. Secondly, the influence and mechanism of rare earth oxides on the wear resistance of Al2O3 ceramics are introduced. Finally, the future research and development directions of rare earth oxides used in Al2O3 wear-resistant ceramics are prospected. The results show that different rare earth oxides have different effects on the wear resistance of Al2O3 ceramics, but not all the doped rare earth oxides can improve the wear resistance of Al2O3 ceramics. The doping of one component or multi component rare earth oxides, such as Y2O3, La2O3, CeO2, Nd2O3, Sm2O3, Tb4O7, Yb2O3, Gd2O3, Er2O3, and Lu2O3, has a positive effect on the wear resistance of Al2O3 ceramics, among which Gd2O3, Er2O3, and Lu2O3 can enable Al2O3 ceramics to exhibit the best wear resistance at lower doping levels; on the contrary, the doping of rare earth oxides, such as Eu2O3, Ho2O3, and Tm2O3, has a negative impact on the wear resistance of Al2O3 ceramics. Therefore, for the design and production of Al2O3 wear-resistant ceramics, it is crucial to choose suitable rare earth oxides for the preparation of high wear-resistant products.